137k views
1 vote
Answer the last one please answer fast

Answer the last one please answer fast-example-1

1 Answer

2 votes

Answer:

Explanation:

Put the equation in the form ax+by+c=0:


y√(3) =8x+√(3) \\=>8x-√(3) y+√(3) =0

Check the solutions:


(0,-1):


8(0)-√(3) (-1)+√(3) =2√(3)

So this is not a solution.

(
(√(3) ,9):


8√(3) -9√(3) +√(3) =0

So this is a solution

User Krishna Ch
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.